THE CRIMINALIZATION OF COVERING MUSIC SONGS WITHOUT PERMISSION: EXPLORING THE LEGAL IMPLICATIONS, PIRACY, TAX LAWS, AND ACTS OF CORRUPTION - Edi Ribut Harwanto (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
Enforcement of criminal law within the Copyright Act alone is insufficient to effectively address acts of piracy, duplication, cover songs, distribution, and management of copyrighted music and songs. Offenders without a license/permit are subject to both criminal and civil sanctions. The Criminal Law No. 28 of 2014 on Copyright also imposes criminal sanctions for pirates, cover songs, and music rearrangement without permission from copyright holders or related rights. This study identifies two main issues. Firstly, there is a weak implementation of criminal sanctions in copyright law, particularly concerning juridical aspects in the formulation of criminal law provisions (penal policy). Secondly, there is a need for understanding among copyright holders, related rights, and offenders to operationalize law enforcement by employing other relevant laws outside copyright law. The use of criminal acts of corruption and taxation can be an effective effort to protect the law and ensure legal certainty. To address these issues, this research employs a socio-legal approach, which combines doctrinal studies with social studies. This integration is based on the belief that the rule of law cannot operate in isolation when dealing with copyright piracy of songs and music in Indonesia. The post-positivism paradigm underpins this study, acknowledging the reality based on experience while maintaining the researcher's objectivity towards the subject. Empirical verification, hypothesis testing, and maintaining a clear distinction between the researcher and the object under study are emphasized throughout this research.